Interactive Methods of Teaching Russian Literature in Uzbek Language Schools - Alina Khasanova Maratovna; Gulmira Eskaraeva Beketovna (Genius Publishing Group, 2022)
To date, there is a need to introduce into the educational the process of innovative methods and new pedagogical technologies, designed to ensure the individualization of education and upbringing, to develop student autonomy, as well as to promote the preservation and strengthening of health. This article presents interactive methods, which are fully meet these requirements. The issues of interactive learning are devoted to the work of many scientists and specialists: S.Yu.Kurganova, V.Kh.Sheine, M.V.Klarina and others. The author believes, that implementation of training using interactive methods teacher must have teaching skills and must be brought to a high degree of teaching and educational skill, reflecting a special polished methods and techniques.
Keywords: Interactive; ICT; TTA; Methodology